Properties of plywood from planted Paraserianthes falcataria and Neolamarckia cadamba - Mohd Nazri Wan Abd Rahman, Wan; Fitri Saâ€™ad, Muhammad; Yuziah Yunus, Nor (International Journal of Engineering and Technology, 2018)
This study is focused on a new wood material for plywood production in Malaysia. Depleting supply of big diameter log from virgin forest had contributed to discovering use of fast-growing species from a systematic forest plantation scheme. Batai (Paraserianthes falcataria) and Kelampayan (Neolamarckia cadamba) were used as raw materials to manufacture the new plywood product. This study also investigated the chemical properties for both species to further justify the plywood properties. The chemical analysis is carried out according to TAPPI Standard. The tree samples were harvested from the trial plot in UiTM Jengka Pahang and sent to plywood mills nearby for plywood production. Logs are peeled into different size of veneer (1.5 meter and 2.7 meter) and thickness. The plywood was composed in five layers and seven layers with 12 mm thickness and used melamine urea formaldehyde (MUF) as a binder based on commercial industry production. Boards were cut and tested according to Japanese Agriculture Standard (2014) at Forest Research Institute Malaysia (FRIM). Based on minimum standard requirement, results showed that both species are suitable to be made into plywood for general use and structural (decorative) purpose. In addition, increased veneer layers improved the board strength.Â Â